Early changes in peritumorous oedema and contralateral white matter after dexamethasone: a study using proton magnetic resonance spectroscopy. Issue 6 (June 1997) - Chumas, P; Condon, B; Oluoch-Olunya, D; Griffiths, S; Hadley, D; Teasdale, G
Abstract : AIMS: To study the mechanism of action of steroids in patients with peritumorous oedema. METHODS: To investigate early cerebral metabolic changes proton magnetic resonance spectroscopy (1H-MRS) was used before and 11 to 14 hours after treatment with dexamethasone (12 mg oral loading and 4 mg four times daily maintenance). Nine patients (two men, seven women, mean age 54) with pronounced oedema associated with various intracranial tumours (two astrocytomas, three meningiomas, two glioblastoma, and two metastases) were examined using MRI and MRS. SE1500/135 volume selected MRS (mean volume 21 ml) were performed on an oedematous region and a contralateral region. All spectra were acquired with and without water suppression. Metabolite peak area ratios were determined. RESULTS: Regions of oedema had significantly (P < 0.01) higher unsuppressed water than the contralateral regions, as expected. There was no change at this early time point after dexamethasone. The ratio of the area of choline containing compounds to that creatine and phosphocreatine compounds was determined after which the serial ratios of these before and after were calculated (a serial ratio of 1.0 would indicate no change in the choline to creatine ratios after steroid administration). The mean serial ratios for the area of oedema were 1.02 (SEM 0.08) and 1.10 (0.08) for the contralateral volume of interest, indicating no significant changes. However, significant changes (P < 0.02) were found in the N-acetyl-aspartate (NAA)/choline serial ratios (0.86 (0.06) in the area of oedema, 1.20 (0.10) in contralateral brain) and the NAA/creatine serial ratios (0.86 (0.08) for the oedema, 1.25 (0.11) in contralateral brain). CONCLUSIONS: Such rapid changes may be explained either by relatively large alterations in the relaxation characteristics of NAA or, more controversially, by actual changes in the amounts of NAA. It is proposed that steroids act primarily by causing early metabolic changes that are later expressed in improvements in intracranial volume relations.